CHRISTIANS’ TOLERANCE OF MUSLIMS’ RELIGIOUS SOUNDS IN TANA TORAJA - Akbar Akbar; Syani Bombongan Rantesalu (Balai Penelitian dan Pengembangan Agama Makassar, 2023)
Despite extensive research on religious tolerance, there is little empirical research on the sensitive issue of sacred sound, particularly in minority Muslim areas. This issue emerged in Indonesia following the Minister of Religious Affairs' policy to regulate loudspeakers from mosques, which were seen as potentially causing intolerance. Religious tolerance remains well established in Muslim-minority areas such as Tana Toraja, even though mosques are allowed to sound freely. The present research explores the traces of Christian tolerance to the sound of mosques heard by minority Muslims. This qualitative study applied an interpretive phenomenological research design with religious leaders, academics, students, and Christian community members as data sources. Garret Keizer's noise theory and Robert Hayden's concept of tolerance categorisation were used to analyse the data. The research results indicated tolerance between religious communities as the mosque sound was accepted as a natural-cultural sound rather than a theological sound. Therefore, intolerance potential arises from the sociological rather than theological dimension. This study suggests that religious tolerance should be shaped by a professional understanding of one's faith and an appropriate response to the religious practices of others. External factors such as social, economic, and political issues, often framed as religious issues, are at the root of religious intolerance. In order to counter the risk of intolerance, a systematic and continuous socialisation of a moderate understanding of all elements of the religious communities is required.